Copper-Catalyzed Intramolecular α-C–H Amination via Ring-Opening Cyclization Strategy to Quinazolin-4-ones: Development and Application in Rutaecarpine Synthesis - Patel, Srilaxmi M.; Chada, Harika; Biswal, Sonali; Sharma, Sonika; Sharada, Duddu S. (Synthesis, 2019)
A copper-catalyzed intramolecular α-C–H amination has been developed for the synthesis of quinazolin-4(3H)-one derivatives from commercially available isatoic anhydride and primary and secondary benzylamines via ring-opening cyclization (ROC). This method shows good functional group tolerance and allows access to a range of 2-aryl, 2-alkyl, and spiroquinazolinone derivatives. However, 2-methylquinazolin-4(3H)-one was synthesized from 2-amino-N-isopropylbenzamide by C–C bond cleavage, and N-benzyl-2-(methylamino)benzamide afforded 1-methyl-2-phenylquinazolin-4(1H)-one along with 2-phenylquinazolin-4(3H)-one by N–C bond cleavage for aromatization. It is the first general method to construct the potentially useful 2-methylquinazolin-4(3H)-one by copper-catalyzed intramolecular C–H amination. Also this ROC strategy has been successfully applied to the synthesis of quinazolinone alkaloid rutaecarpine.
Keywords: intramolecular C-H amination; ring-opening cyclization; rutaecarpine; quinazolin-4(3H)-one; 2-methylquinazolin-4(3H)-one